Analisis Kinerja Pada Dinas Pendapatan Daerah Kota Sorong Provinsi Papua Barat - Kondjol, Ariance Sara (JURNAL RISET BISNIS DAN MANAJEMEN, 2014)
The objective of this study is to analyses the public service performance in Dinas Pendapatan Daerah, Sorong City, North Papua Province based on respondent perception as service user. The resesearch design is descriptive. Population of this study is the service users and the head of Dinas Pendapatan Daerah, Sorong City, North Papua Province. The sampling method is accidental method. Analysis result that the 12 aspect of performance in Dispenda is high and the highest is the aspect of accountability but the lowers is life sustainability. Keywords : performance analysis, public services